3D Printed porous tissue engineering scaffolds with the self-folding ability and controlled release of growth factor. (December 2020) - Lai, Jiahui; Li, Junzhi; Wang, Min
Abstract: Abstract : This study investigated a new strategy for fabricating porous scaffolds with the self-folding ability and controlled release of growth factors (GFs) via 3D printing. The scaffolds were a bilayer structure comprising a poly(D, L -lactide- co -trimethylene carbonate) scaffold for providing the shape morphing ability and a gelatin methacrylate scaffold for encapsulating and delivering GF. The structure, shape morphing behavior, GF release, and its effect on stem cell behavior were studied for new scaffolds. The results suggest that these scaffolds have great potential for regenerating tissues such as blood vessels. This work also contributes to developments of 3D printing in tissue engineering.